A Comparison of Learning Using Animated Video and Padlet Viewed From the Ability of Writing Skills Elementary School Students - Yuli Artanti; Syafruddin Syafruddin; Sendi Ramdhani (Eduvest - Journal of Universal Studies, 2025)
This study aims to compare the effectiveness of animated video and Padlet as learning media in improving elementary school students' writing skills. The research employs a mixed-method approach, combining quantitative and qualitative analyses. The study was conducted with 33 fifth-grade students at SDN Jatiwarna 2, Bekasi, using a quasi-experimental design with pre-test and post-test evaluations. The results indicate that both media positively impact students' writing abilities; however, Padlet is more effective in enhancing students' engagement, creativity, and collaboration. Students who utilized Padlet demonstrated better writing structures, improved idea development, and slot deposit 5000 higher motivation due to interactive peer feedback. Meanwhile, animated video effectively increased students' understanding of writing steps but lacked interactive elements. Statistical analysis confirmed a significant difference in learning outcomes between the two media, with Padlet achieving higher effectiveness. These findings suggest that integrating Padlet into writing instruction can foster a more interactive and engaging learning environment, ultimately improving students' writing proficiency.